Republic of Uzbekistan : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Uzbekistan. (IMF Staff Country Reports; Country Report ;, 2022)
Uzbekistan embarked on an ambitious reform path in 2017, starting to liberalize its economy after years of state control. Incomes are still relatively low compared to other emerging economies and the role of the state is still large. Uzbekistan weathered the pandemic relatively well. Strong fundamentals, ample policy buffers, and high gold prices allowed the authorities to take strong actions to mitigate the impact of the pandemic and growth accelerated to 7.4 percent in 2021.